White Kabesak (Acacia Leucophloea RoxB) Leaves Utilization in Concentrate on Fermentation Products and In Vitro Gas Production - Lawa, E.D. Wie; Chuzaemi, S; Hartutik, Hartutik; Marjuki, Marjuki (Journal of Tropical Life Science, 2020)
This study aimed to evaluate gas production and in vitro fermentation products from feed containing leaves of white kabesak (acacia leucophloea Roxb.)Willd. Feed was composed of a ratio of 60% natural grasses and 40% concentrate. The treatments were used levels of white kabesak leaves in concentrates i.e. 0, 10, 20, 30 and 40% in the dry matter (DM) basis as treatments, R0, R1, R2, R3 and R4 treatments, respectively. The results showed that inclusion of acacia leucophloea leaves in concentrate increased organic matter and crude fiber contents but decreased the crude protein content. Increasing level of acacia leucophloeaÂ  leaves in concentrate decreasedÂ  gas production (b, ml / 500 mg DM) from 198.29 (R0) to 139.93 (R4). The gas production rate (c, ml /hour) was relatively constant between 0.034 to 0.036 on R0 - R3 and 0.028 on R4. Gas production at 48 hours incubation (y, ml / 500 mg DM) decreased from 153.38 (R0) to 103.23 (R4). The NH3 concentrations ranged from 6.17-7.31 mg / 100 ml and the total VFA was 83.07-91.96 mM. The lowest C2 / C3 ratio was in R2 (2.63). The highest IVDMD was 50.18-67.14% in R0 and the lowest IVOMD was 55.04-71.35% R4. The use of acacia leucophloea leaves at level 20% in concentrates as supplements was more efficient in reducing gas production and in vitro fermentation products.